2021
DOI: 10.21203/rs.3.rs-118288/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association of CSF proteins with tau and amyloid β levels in asymptomatic 70-year-olds

Abstract: BackgroundIncreased knowledge of the evolution of molecular changes in neurodegenerative disorders such as Alzheimer’s disease (AD) is important for the understanding of disease pathophysiology and also crucial to be able to identify and validate disease biomarkers. While several biological changes that occur early in the disease development have already been recognised, the need for further characterization of the pathophysiological mechanisms behind AD still remains.MethodsIn this study, we investigated cere… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 79 publications
(103 reference statements)
0
5
0
Order By: Relevance
“…Unique to this study was the inclusion of a more comprehensive set of CSF biomarkers relevant to AD, neurodegeneration, and neuroinflammation. We replicated numerous protein associations with p-tau, but found less replication for proteins previously associated with amyloid, 77,85 which could be due to differences in the exact amyloid measures used (Note S4 in supporting information). We also saw an imbalanced distribution of protein associations by biomarker, with neurogranin having by far the greatest number of protein associations and IL-6 having none (Note S5 in supporting information).…”
Section: Discussionmentioning
confidence: 70%
“…Unique to this study was the inclusion of a more comprehensive set of CSF biomarkers relevant to AD, neurodegeneration, and neuroinflammation. We replicated numerous protein associations with p-tau, but found less replication for proteins previously associated with amyloid, 77,85 which could be due to differences in the exact amyloid measures used (Note S4 in supporting information). We also saw an imbalanced distribution of protein associations by biomarker, with neurogranin having by far the greatest number of protein associations and IL-6 having none (Note S5 in supporting information).…”
Section: Discussionmentioning
confidence: 70%
“…These nominally associated proteins included many proteins known to form intracellular or extracellular deposits in disease( 71 ), including APP, TTR, B2M, APOA1, APOA2, APOA4, APOC2, APOC3, LYZ, CST3, SOD1, IGHG1, IGHG2, IGHG3, and HBB (Supplementary Table 6). Although individual protein associations and pathway enrichment have tended to be the focus of previous work, several studies have reported similar widespread enrichment among the proteome, including a case-control study of AD diagnosis with 487 of 1,968 (24.7%) of proteins nominally associated with AD diagnosis( 75 ) and a study of protein correlations with CSF total tau, ptau, and Aβ42 where 63 out of 106 proteins (59.4%) were associated with at least one of the biomarkers( 45 ). Indeed, one core feature of AD proteomics work historically has been the identification of numerous AD-associated proteins that nonetheless do not replicate upon further study( 36, 37 ).…”
Section: Discussionmentioning
confidence: 86%
“…One of the major trends in AD research has been the movement toward a biomarker-based definition of AD( 11 ). Recent CSF proteomics work in AD has explored the relationship between CSF protein levels and various AD biomarkers, especially measures of amyloid and tau pathology( 34, 45 ). We replicated numerous previously reported protein associations with CSF levels of ptau (e.g., SMOC1, BASP1, and GAP43)( 34, 45 ), but failed to replicate any of the proteins significantly associated with CSF amyloid, though we note that our analysis used Aβ42/Aβ40 as the outcome rather than Aβ42 since Aβ42/Aβ40 is considered to be a better biomarker for AD than Aβ42 alone( 46 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown dementia to be a slowly progressive disease and lesions in the brain could be shown as early as 10-15 years before onset of clinical symptoms [9][10][11]. More recently, biomarker-based diagnostics such as amyloid-␤ and tau proteins detected using positron emission tomography (PET) scans and cerebrospinal fluid (CSF) analysis have been recognized as promising markers for pathology [12]. While these biomarkers offer high predictive ability, their high cost and invasive procedures have hindered their widespread use [13].…”
Section: Introductionmentioning
confidence: 99%